Elimination of PPV and PNRSV through thermotherapy and meristem-tip culture in nectarine - Manganaris, George A.; Economou, Athanasios Sotirios; Boubourakas, I.N.; Katis, Nikolaos I. (My University, 2003)
The plum pox virus (PPV) and prunus necrotic ringspot virus (PNRSV) cause serious disease problems in stone-fruit trees. In this work, the possibility of obtaining plant material free from these viruses through thermotherapy and meristem-tip culture from infected nectarine shoots (Prunus persica var. nectarina Max, cv. ''Arm King'') was studied. In addition, the detection of these viruses in in vitro cultures and young acclimatized plantlets with double antibody sandwich-enzyme-linked immunosorbent assay (DAS-ELISA) and multiplex reverse transcriptase-polymerase chain reaction (RT-PCR) was studied. Meristem-tip explants (0.8–1.3 mm) derived from sprouted buds of winter wood and spring shoots from field grown plants had a 2–5% regeneration response. However, application of thermotherapy to potted nectarine trees (3 weeks at a maximum temperature of 35°C) facilitated excision of longer meristem tips (1.3–2.0 mm) that resulted in a significantly higher regeneration response (38%) in woody plant medium (WPM) without plant growth regulators. Such explants formed multiple shoots with the addition of 8 M benzylaminopurine and 0.8 M indoleacetic acid. When they were tested for the presence of PPV and PNRSV, 86% and 81% were found to be virus-free as detected by DAS-ELISA and multiplex RT-PCR, respectively. Individual shoots excised from virus-free cultures readily rooted in vitro (half-strength WPM plus 2 M indolebutyric acid) and grew to plantlets. The combination of an efficient protocol for virus elimination and the establishment of highly sensitive diagnostics resulted in the production of nectarine plants free from PPV and PNRSV.
Keywords: Meristem culture; Plum pox virus; Prunus necrotic ringspot virus; Prunus persica; Virus; Indexed